Parenting practices of farming parents in fostering independence among children aged 5–6 years amid time constraints - Harianti, Dini Septi; Putro, Khamim Zarkasih (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2026)
Background: Children’s independence is an important aspect of early childhood development that is generally fostered through intensive parental involvement. However, children in farming families often experience limited interaction with their parents due to agricultural work activities. Objective: This study aimed to analyze the parenting strategies employed by farmer parents in fostering the independence of children aged 5–6 years in Pendem Village. Methods: This qualitative descriptive study involved four farmer parents and four children. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Result: The findings showed that children demonstrated physical independence through their ability to eat, bathe, dress, and manage personal needs independently, while emotional independence was reflected in their ability to regulate emotions and adapt to social environments when their parents were working. Independence was fostered through habituation, simple responsibilities, direct experiences, and support from the village community. The novelty of this study lies in the finding that limited parent–child interaction does not hinder children’s independence but instead fosters a contextual parenting pattern based on direct experience and community support. Conclusion: Limited parent–child interaction in farming families does not necessarily impede the development of children's independence. Instead, farmer parents foster independence through contextual parenting practices that emphasize habituation, responsibility, direct experiences, and community support, enabling children to develop both physical and emotional independence from an early age.